HE4, A New Potential Tumor Marker for Early Diagnosis and Predicting of Breast Cancer Progression - Nazanin Mirmohseni Namini; Alireza Abdollahi; Monireh Movahedi; Amirnader Emami Razavi; Reza Saghiri (Iranian Society of Pathology, 2021)
Background & Objective: This study examined the potential of human epididymis protein 4 (HE4) as a marker in early diagnosis or as a prognostic factor for breast cancer (BC) patients.Methods: A total of 31 patients diagnosed with BC were enrolled in the study between 2008 and 2018. The mRNA and protein expression levels of HE4 were analyzed by immunohistochemistry (IHC) and real-time polymerase chain reaction (PCR) in the BC tissue and the non-tumoral adjacent tissue. Using ELISA technique, HE4 plasma levels were also measured in 43 BC patients compared to 43 healthy individuals. The correlation between HE4 expression and clinicopathological features was then investigated.Results: An increase in HE4 expression was observed at mRNA and protein levels in the BC group compared to the control group (p <0.01, p <0.0001, respectively). In addition, the relative expression of HE4 mRNA in BC patients showed a significant correlation with the differentiation grade of cancer cells (p <0.001). Plasma levels of HE4 was also associated with grade (p <0.0001), stage, and tumor size in BC patients (for both p <0.01). Patients with metastatic BC (p <0.01), lymphatic invasion, and lymph node involvement (for both p <0.05) showed significantly higher plasma levels of HE4 expression than patients without metastasis.Conclusion: According to our findings, upregulation of HE4 is probably related to invasive BC phenotype, and measuring plasma levels of HE4 could be useful as a screening test in early diagnosis of BC.